Treatment of Cancer-Associated Thrombosis: An Update - Voigtlaender, Minna; Rolling, Christina; Hart, Christina (Hämostaseologie, 2024)
Patients with cancer are at increased risk of venous thromboembolism (VTE). Treatment of VTE remains challenging due to a significant risk of both VTE recurrence and bleeding compared with patients without underlying malignancy. Moreover, patients with cancer often present with several comorbidities such as tumor- or treatment-induced bone marrow failure, renal impairment, and extensive concomitant anticancer or supportive medication, resulting in potential drug–drug interactions. Further challenging circumstances include gastrointestinal (GI) disorders, in the context of a GI intraluminal tumor itself, GI surgery, or systemic therapy-induced GI toxicity. However, treatment options and study data in the management of cancer-associated thrombosis (CAT) have expanded over the last few years. As a result, it is becoming increasingly important to assess the patient's individual risk of bleeding and its comorbidities, and the patient's personal preferences. Prospectively, further therapeutic strategies such as factor XIa inhibitors are under clinical investigation. The aim of our narrative review is to summarize the current literature on therapy options for CAT, including common treatment situations encountered in the management of patients with cancer.
Keywords: cancer; thrombosis; treatment; anticoagulants; bleeding